Plan de aseguramiento metrológico en los servicios de UCI y salas de cirugía para la clínica universidad de la sabana (2021)
Introduction: At the Universidad de la Sabana Clinic, the need to evaluate the tools used in the maintenance and verification processes of biomedical equipment was identified. This in order to identify within the current regulations in Colombia that biomedical equipment requires calibration processes or performance evaluation. Therefore, it is proposed to carry out a metrological assurance plan, where all the information on the technical specifications of the equipment present in the service is collected. Objective: Generate the metrological assurance plan in the intensive care unit (ICU) service and the surgery room service of the Universidad de la Sabana Clinic. Methodology: In order to generate a support tool for the Biomedical Engineering department in the process of the maintenance schedule for the year 2022. The creation of the metrological assurance plan is developed in 3 phases which allow the verification of the inventory in both services, compilation of technical specifications of the equipment to be evaluated, selection of equipment for calibration processes and those that will be handled through performance evaluation. Finally, an adaptation of existing formats to specific technologies is generated. Results: Inventory of ICU services and surgery rooms is validated, in order to identify the biomedical equipment of the services. From these, it was possible to recognize the equipment that requires calibration processes by a certified laboratory and the equipment submitted to performance evaluation. For all the biomedical equipment present in both services, the database is complemented where the technical specifications of each equipment are shown. And for the teams selected for the performance evaluation process, the corresponding formats were adapted. Conclusions: The database was adapted as part of the solution that allows identifying the biomedical equipment of the ICU services and surgery rooms. This format will allow the institution to organize the technology according to its technical file, as well as to identify if the biomedical equipment requires metrology processes or evaluation performance according to the regulations. When reviewing the documentation of the current metrology regulations in Colombia, it is found that there is no clarity of the processes that are carried out with each biomedical equipment according to its risk classification. This is why the equipment is chosen according to its operating principle to be subjected to a performance evaluation process. It is identified that the application process of the metrological assurance plan will allow the institution to start with a cost optimization process. It will guarantee compliance with current regulations, the reduction of adverse events due to biomedical equipment and the extension of years of useful life of the technology.